2013
DOI: 10.1021/la400938j
|View full text |Cite
|
Sign up to set email alerts
|

Poly(azobenzene acrylate-co-fluorinated acrylate) Spin-Coated Films: Influence of the Composition on the Photo-Controlled Wettability

Abstract: The wetting properties of spin-coated films of copolymers based on azobenzene and fluorinated units have been investigated. The copolymers, denoted as poly(Azo-co-AcRf6), have been synthesized by free-radical polymerization of different proportions of acrylate monomers bearing either an azobenzene group or a semifluorinated side chain. The UV-visible spectroscopy analysis of the different spin-coating films through a cycle of UV and visible light irradiation indicates the reversible trans-cis isomerization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
(67 reference statements)
3
25
0
Order By: Relevance
“…In this paper, the authors have firstly investigated reversible control of surface wettability of polyimides having azobenzene group on their side-chain by UVVis light irradiation. It is previously reported that the reversible trans-cis isomerization of azobenzene groups through UV-Vis irradiation is accompanied by fast and large changes in both geometry dipole moment [18,19], and this fact is expected to affect the reversible wettability change (Fig. 1).…”
Section: Introductionmentioning
confidence: 90%
“…In this paper, the authors have firstly investigated reversible control of surface wettability of polyimides having azobenzene group on their side-chain by UVVis light irradiation. It is previously reported that the reversible trans-cis isomerization of azobenzene groups through UV-Vis irradiation is accompanied by fast and large changes in both geometry dipole moment [18,19], and this fact is expected to affect the reversible wettability change (Fig. 1).…”
Section: Introductionmentioning
confidence: 90%
“…[1][2][3] One such smart material is the stimuliresponsive polymeric surface with tunable wettability under different external conditions, 4 such as pH, 5-8 electric potential, 9,10 light, [11][12][13][14] temperature, [15][16][17][18] and gas. 19 This feature enables the material to have applications in many areas, including controlled release platform, 20 ion pump, 21 and water/oil separation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the polymer grafting, functional polymer coating that can be used directly would be more attractive in industrial fields because of its simple implementation process. [12][13][14][15] More recently, Yuan and Luo et al fabricated two types of smart fiber membranes by depositing pH-responsive copolymer fibers on a stainless steel mesh (SSM) through electrospinning for controllable oily water separation. 19,24 Poly(acrylic acid) (PAA) is a typical pH-sensitive hydrophilic polymer with pKa 5 4.7.…”
Section: Introductionmentioning
confidence: 99%
“…Their tendency toward self‐assembly and low‐surface free energies also makes them promising components in photoresponsive materials …”
Section: Introductionmentioning
confidence: 99%